2018
DOI: 10.1111/gcb.14058
|View full text |Cite
|
Sign up to set email alerts
|

Arctic moistening provides negative feedbacks to riparian plants

Abstract: Arctic moistening will affect the circumpolar forested riparian ecosystems. Upward trends observed for precipitation in high latitudes illustrate that the moistening may be underway to influence the woody biomass production near the inland waters, lakes and streams with effects on carbon pools and fluxes. Although the flooding and waterlogging tolerance of seedlings has been investigated, our understanding of responses in mature trees is still limited. Here we employ tree-ring δ C and width data from a subarct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 106 publications
(196 reference statements)
0
2
0
Order By: Relevance
“…In addition, high spring temperatures have enhanced snow and soil frost melting and consequently tree growth (Hordo et al 2011;Helama et al 2013). Apart from temperature, the Arctic moistening affects the Arctic forests of northern Fennoscandia through increased precipitation and cloud cover (Helama et al 2018). However, growth response to precipitation has generally been weak in northern boreal forests (Salminen et al 2009;Korpela et al 2011;Fleischer et al 2022), even though our previous results indicated that water availability and drought may influence tree growth also at the high northern latitudes (Henttonen et al 2014).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In addition, high spring temperatures have enhanced snow and soil frost melting and consequently tree growth (Hordo et al 2011;Helama et al 2013). Apart from temperature, the Arctic moistening affects the Arctic forests of northern Fennoscandia through increased precipitation and cloud cover (Helama et al 2018). However, growth response to precipitation has generally been weak in northern boreal forests (Salminen et al 2009;Korpela et al 2011;Fleischer et al 2022), even though our previous results indicated that water availability and drought may influence tree growth also at the high northern latitudes (Henttonen et al 2014).…”
Section: Introductionmentioning
confidence: 89%
“…Large-scale greening detected in northern regions since the early 1980s based on remote sensing vegetation data is thought to be caused by climate warming (Myneni et al 1997;Nemani et al 2003). Fennoscandia belongs to the region where warming has been extensive since the 1970s with a strong Atlantic influence modifying the seasonal climatic patterns (Marshall et al 2018) and affecting vegetation and tree growth (Henttonen et al 2017;Helama et al 2018).…”
Section: Introductionmentioning
confidence: 99%